Pengaruh Pemberian Dedak Padi Terhadap Penampilan Produksi Ayam Broiler - Aris Munandar; Wisye M Horhoruw; Godlief J Joseph (Fakultas Pertanian, Universitas Pattimura, 2020)
Broilers, are superior breeds from crosses from type of chicken that have high productivity, especiallyin producing meat. The rapid growth rate in broilers is always influenced by the intake of a lot of feedconsumption. This is a problem for farmers who want broilers to consume low feed but the carcassweight increases, because almost 70% of production costs are determined by the cost of feed. Thepurpose of this study was to analyze the influence of addition rice bran in broiler feed on its performance.This study used a Completely Randomized Design with 4 treatments namely P0 (commercial feedwithout the addition of rice bran); P1 (commercial feed + 10% rice bran); P2 (commercial feed + ricebran 20%) and P3 (commercial feed + rice bran 30%), each treatment have 5 replications. The variablesobserved were feed consumption, body weight gain, feed conversion, carcass weight and carcasspercentage. The results showed that the addition of rice bran in each treatment (P1, P2 and P3) was notsignificantly different (P> 0.05) with treatment without the addition of rice bran (P0). The results of thisstudy concluded that the ration of broiler chicken feed can be supplemented with rice bran up to 30%.